Feasibility of Regional Security Framework in Northeast Asia - Kyung Hwan Cho (Journal for Peace and Nuclear Disarmament, 2020)
In this era when the geopolitical center of gravity is shifting to Northeast Asia where a strategic competition between great powers is resurgent, there are new opportunities for cooperation in the region in spite of significant challenges. In order to overcome traditional tensions, ongoing disputes, and struggles over hegemony in the region, it is necessary for the countries of the region to change the way they think and act. In that regard, it would be beneficial to develop some form of multilateral cooperation that promotes peaceful coexistence and mutual prosperity. By scrutinizing the current situation with an eye to the requirements and variables of building a multilateral security cooperation architecture, this article analyzes why Northeast Asia has yet to establish such a framework and tries to determine whether the region has the potential to do so. It concludes that while South Korea, Japan, and Russia are in favor of a multilateral approach, the United States, China, and North Korea are less enthusiastic about the idea. However, the United States and China recently have developed a basis for multilateral security cooperation from their experiences, especially in North Korean issues. A related question is how the countries involved would institutionalize cooperation. This analysis concludes that the best approach would be to start with a small but specific undertaking based upon existing architectures that can utilize existing resources. This idea can be realized by first holding a regional summit to discuss common security issues.